Intelligent elderly care II - Lim, Jun Rong (2015)
As statistics show that dementia cases is rising over next few decades, the need for better quality healthcare technologies for these patients are required. Caretakers who are mainly families of these patient are mostly not medical well-trained or busy with work supporting the family. Technologies is also made to assist and help ensuring the safety and well-being of this group of patients and at the same time allows those patients to carry out their daily activities more independently. In this project, I will be implementing an outdoor Intelligent Elderly Care system which targets consumers especially for elderly with dementia illness and their caretakers. This system breaks down into two components which are Home Exit/Entry Notification System and Intelligent GPS Tracking System. Home Exit/Entry Notification System will help notify the caretakers when the elderly goes out of house or returns home. This can be done by elderly tapping the RFID card on the device during exiting and entering of house. An SMS will be sent and notify the caretaker. Next, Intelligent GPS Tracking System will take over to monitor the positon of the elderly at outdoor. With the help of Global Positioning System, the location of the elderly can be found and display on the Google map in two different viewing platforms. The caretaker can either view using webpage which can be accessed anywhere and anytime on mobile devices with internet data or using Graphic User Interface on the local server at home. Boundary Limitation System is also implemented in this function to monitor if the elderly has travelled outside the specified boundary radius of the house. An SMS will be sent and notify the caretaker if the elderly has exceeded the distance boundary. With these two monitoring systems, the elderly can be monitored from the start to the end of the trip and ease the burdens on the caretakers.